Emergence and partial characterization of rice stripe necrosis virus and its fungus vector in South America - Morales, Francisco José; Ward, Elaine; Castaño, Mauricio; Arroyave, José A.; Lozano Potes, Iván; Adams, Michael J. (Springer, 1999)
A new disease of rice, known as ‘entorchamiento’ (crinkling), was first noticed in the Department of Meta, Colombia, in 1991. Symptoms include seedling death, foliar striping and severe plant malformation. Tissue extracts and purified preparations from diseased rice plants, contained virus-like particles ca. 20?nm in diameter, with a bimodal length of 260 and 360?nm. Particle aggregates were also observed in the cytoplasm of infected rice leaf cells. Electrophoretic analyses of purified preparations and dsRNA extracts, revealed a single protein species of M 22,500, and four dsRNA bands ca. 6300, 4600, 2700 and 1800?bp in size. Cystosori, characteristic of plasmodiophorid fungal vectors of plant viruses, were consistently observed in the roots of diseased rice plants. PCR and sequence analyses of amplified fungal DNA products from infected rice roots, revealed that the putative fungus vector was Polymyxa graminis. A Western blot of tissue extracts obtained from ‘crinkled’ rice plants from Colombia, using antiserum against a West African isolate of rice stripe necrosis furovirus (RSNV), resulted in the detection of a protein band of approximately M 22,000. The RSNV antiserum recognized the Colombian virus isolate in serologically specific electron microscopy tests. These results confirm the presence of RSNV in the Americas.